Analysis of an explosion accident at Dangyang Power Plant in Hubei, China: Causes and lessons learned. (February 2018) - Fu, Gui; Zhou, Lin; Wang, Jianhao; Shi, Meng
Highlights: A new accident model was proposed for analyzing Dangyang Power Plant explosion. Unsafe acts produced by staff from different levels were identified. Specific flaws in safety management system and safety culture were found. Preventive measures and the application of analysis results in safety training were discussed. Abstract: On August 11, 2016, an explosion of a high-pressure steam pipeline occurred at a power plant in Dangyang City, Hubei Province, China. The accident killed 22 people and 4 people were injured. The causal factors of the accident were analyzed to prevent such catastrophe in the future. The entire accident process was divided into three sequential events for respective analysis based on timeline. Furthermore, a new model demonstrating the relationships among different causal factors was proposed and applied for this accident analysis. With respect to the power plant, the deficiencies from five causal categories were identified, which clearly demonstrated the accident mechanism from immediate causes to root causes. The results of the analysis indicated that unsafe acts performed by staff from different levels in power plant led to unsafe conditions, which were due to three factors, i.e., staff's inadequate safety knowledge, weak safety awareness and bad safety habits. The elements in safety management system (e.g., "procurement, " "determination of applicable legal requirements and other requirements") were not implemented and maintained. Moreover, the staff did not reach a consensus on specific safety beliefs (e.g., "safety is the first priority, " "the importance of top management commitment"), which indicated poor safety culture in the organization. Finally, in order to prevent the recurrences of similar accidents, the major lessons learned from this explosion were proposed and the application of the analysis results for related safety training was discussed.